(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Many factors have been proposed to be associated with higher mortality in patients on continuous ambulatory peritoneal dialysis (CAPD). However, the relative importance of these factors may differ among patients with different characteristics. We evaluated survival of patients on CAPD and its influencing factors in Iran. Materials and Methods. We enrolled 282 patients on CAPD between 1996 and 2006 at 2 major CAPD centers in Tehran. Patient survival was investigated during this period. Demographic characteristics, laboratory data, dialysis adequacy parameters, residual renal function, peritoneal transport characteristics, and nutritional status were assessed as potential predictors of the outcome. Results. The mean duration of follow-up was 18.4 ± 14.5 months. Sixty patients (21%) died during the studied period. In univariate analysis, age, body mass index, history and duration of hemodialysis before CAPD, diabetes mellitus, blood pressure, patient selection criteria, edema, peritonitis, renal residual function, urine volume, dialysis adequacy, and serum levels of cholesterol, triglyceride, intact parathyroid hormone, calcium, and albumin were predictors of patient survival. Multivariate analysis demonstrated that old age, diabetes mellitus, prior hemodialysis longer than 7 months, low serum albumin, calcium, trigelyceride, and parathyroid hormone levels independently predicted mortality, while the use of angiotensin-converting enzyme inhibitors was associated with a better survival. Conclusions. This study showed that older patients on CAPD and diabetics are at a higher risk of mortality. On the other hand, nutritional and metabolic factors are other predictors of mortality. Especial concern should be applied to good nutrition and treatment of comorbidities in these patients.